SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMA BEASISWA MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) - Sri - Nadriati (LPPM Politeknik LP3I Medan, 2020)
This study aims to produce a decision support system using the Weighted Product (WP) method in the selection of scholarship recipients. With the Weighted Product (WP) method, it can be more efficient and more practical in processing scholarship recipient data. This research was conducted with observation and interviews to collect data. There are 4 criteria as references used in decision making to determine which students are eligible for scholarships. These criteria consist of: cumulative achievement index (C1), number of credits that can be taken (C2), achievement in extracurricular activities (C3), income of parents (C4). And the alternative used when processing the data, namely as many as 10 sample data taken randomly from the many prospective scholarship recipients.